In Spain now! A first-hand story of the fight against fascism and of the use of workers' power for socialism. - McNair, John, 1887-1968 (London : Independent Labour Party, 1936)
1936 SA14-020-004 15, [1] pages : illustrations ; 22 cm. 15X/2/209/99